Er(r)go... - Kalaga, Wojciech (Er(r)go. Teoria - Literatura - Kultura, 2014)
Er(r)go… , … ecology, ecocriticism, ecophilosophy, political ecology, ecological ethics, the memory of the Earth, non-human or rather more-than-human sisters and brothers. Thus, not in the exact order: fading now away into the past, the voyeuristic, disembodied subject, the Self unconscious of its body, but holding the exterior under its perceptual control; instead, a subject inevitably “contaminated” with the exteriority of nature and technology. The abolition of the nature-culture dichotomy. Ecological disasters and the moral panic, the rationing of blame, deconstruction of the technological, the hazards of ecological awareness and the narrations of guilt and responsibility. The freaks of nature and the experience of the curiosity when nature strays from its path; controlled transgression, the fallen mind, the sharpening of intellect, monstrosities and methodological regime, curiosities as methodological tools and Bacon’s rejuvenation of natural philosophy. Literary Darwinists and new positivism, biologically determined culture; culture stripped of its autonomy by natural phenomena. Literature as a means of adaptation and survival; cultural constructivism and evolutionary psychology as a bridge between culture and nature; The Iliad as a tragedy of naked apes; mind or brain, vulgar reductionism and a procession of banalities. Ecopoetry and ecopoetics, nature and destiny, the sound and the fury of civilization, identification with nature, the eschatology of civilizational calamity. The Indian as the Man before the Fall, the footprints of the chieftain and the laws of ethics, the exile from Paradise and the reconciliation in the City of Brotherly Love. The Earth as the beneficiary of postmodernism, the forgetting of nature and the creation of the world, the anthropocentrism of religion and the equality of all creation, silence and Logos, poetic phenomenology, the bird song and the creator concealed in creation. The Self as an entity among other entities, the substance of language and the substance of the world, the transparent eye and the eye of Roentgen. The politics of nature as an oxymoron. The animal as the substance of art and as person, the moral avant-garde of an artist, transspecies communication, the killing of objects. The suffering of animals. The present issue of Er(r)go was prepared under the caring supervision of Marzena Kubisz and Anna Chromik, to whom, on behalf of the Editorial board, I extend our expression of gratitude. Wojciech Kalaga